Clinical Features and Long-Term Outcomes in Very Young Patients with Myocardial Infarction with Non-Obstructive Coronary Arteries - Pablo Juan-Salvadores; Víctor Alfonso Jiménez Díaz; Ana Rodríguez González de Araujo; Cristina Iglesia Carreño; Alba Guitián González; Cesar Veiga Garcia; José Antonio Baz Alonso; Francisco Caamaño Isorna; Andrés Iñiguez Romo (Journal of Interventional Cardiology)
Background. The main cause of acute coronary syndrome (ACS) is coronary artery obstruction due to atherosclerotic plaque growth or thrombus formation secondary to plaque rupture or erosion. However, there is a subgroup of patients with signs and symptoms suggestive of ACS but without relevant coronary artery obstruction on coronary angiography. This population is defined as myocardial infarction with non-obstructive coronary arteries (MINOCA). The present study analyzes the clinical features and outcomes of very young patients with a diagnosis of MINOCA. Method. Nested case-control study of ≤40-year-old patients referred for coronary angiography due to clinical suspicion of ACS. Patients were divided into three groups: patients with obstructive coronary artery disease (CAD), patients diagnosed with MINOCA, and controls with non-coronary artery disease. Results. Of 19,321 coronary angiographies performed in our center in a period of 10 years, 408 (2.1%) were in patients ≤40 years old, and MINOCA was identified in 32 (21%) patients. The cardiovascular risk factors for obstructive CAD and MINOCA were very similar. The incidence of major adverse cardiovascular events (MACE) at follow-up was significantly higher in the MINOCA (HR 4.13 (95%CI 1.22–13.89) and obstructive CAD (HR 4.59 (95%CI 1.90–10.99) patients compared to controls. Cocaine use HR 14.58 (95%CI 3.08–69.02), family history of CAD HR 6.20 (95%CI 1.40–27.43), and depression HR 5.16 (95%CI 1.06–25.24) were associated with a poor outcome in the MINOCA population. Conclusion. Very young patients with MINOCA had a poor prognosis at long-term follow-up, similar to patients with obstructive CAD. Focusing efforts on secondary prevention is essential in this population.